The Influence of Health Education Through Booklet on Knowledge and Practice of Menstrual Hygiene - Nisman, Wenny Artanty; Mutiawati, Dewi Fatma; Nugraheni, Marsita; Milasari, Intan (Jurusan Keperawatan FIKES UNSOED, 2019)
Abnormal discharge from the vagina and infections of the reproductive tract can be prevented by practicing good menstrual hygiene. The ease by which adolescents are able to access information will affect the level of knowledge adolescents have about menstrual hygiene. This study aimed to determine the differences in levels of knowledge and practices of menstrual hygiene in boarding school students in rural and urban areas, before and after having being given health education using booklet media. This study was quasi experimental research. The research took place at MTs Al Falaah Pandak Bantul representing the rural area and MTs Mu'allimat Yogyakarta representing the urban area between December 2016 and January 2017. Knowledge and practice of menstrual hygiene was measured by a questionnaire. There was no statistically significant difference between knowledge of menstrual hygiene in the boarding schools of both rural and urban groups p=0.473, whereas the difference between hygiene practice regarding menstruation in both groups showed a significant difference p=0.000. There were significant differences in the levels of knowledge and practice of menstruation hygiene between the boarding school students in both the rural areas and urban areas before and after health education using a booklet. A higher mean value was indicated by the boarding school students in urban areas.